2011
DOI: 10.1109/tns.2011.2171720
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Low Dose Rate Sensitivity at Ultra-Low Dose Rates

Abstract: We observed ELDRS for dose rates from 10 to 0.5 mrad(Si)/s in commercial and radiation hardened devices. We discuss the implications of the results for radiation hardness assurance of linear bipolar circuits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Defect recombination is efficient and independent of knock-on energy, with only 50% of displacements resulting in defects. 275,276 Diamond-based detectors should withstand a high radiation environment maintaining its unique properties such as fast response, collection efficiency, energy resolution. Radiation hardness is a fundamental property of this material.…”
Section: Discussionmentioning
confidence: 99%
“…Defect recombination is efficient and independent of knock-on energy, with only 50% of displacements resulting in defects. 275,276 Diamond-based detectors should withstand a high radiation environment maintaining its unique properties such as fast response, collection efficiency, energy resolution. Radiation hardness is a fundamental property of this material.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research shows that TID experimental results obtained by different researchers for samples of the same type differs from each other as a result of the different dose rates utilized, sometimes the difference is very great [12,13]. Therefore, some researchers have carried out targeted studies about the influence of dose rate on the TID effect of MOS devices [14], analyzed the influence of dose rate on the sensitive electrical parameters of MOS devices [15], and found the damage enhancement effect of low dose rate [16]. However, for complex digital devices such as anti-fuse FPGA, there is still a lack of scientific understanding about the influence of dose rate on TID effect of FPGA.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the radiation studies on bipolar junction transistors reported so far have mainly focused on experimental results on the radiation induced changes in the measured electrical characteristics of the devices [5]- [7]. However, to the authors' knowledge, very little data regarding noise performance degradation with total dose have been reported for Si bipolar junction transistors [8].…”
Section: Introductionmentioning
confidence: 99%